SELF-ESTEEM AND ACADEMIC ACHIEVEMENT AMONG HIGH SCHOOL STUDENTS IN IMPHAL EAST DISTRICT, MANIPUR - Meitei, Langonjam Chingkheinganba; Devi, Ahanthem Bachandari (International Journal of Research -GRANTHAALAYAH, 2025)
Self-esteem refers to the overall perception of abilities and limitations of an individual. Although it may not directly visible to the outside world but often shows up a discipline, discipline and persistence, which are the essential attributes for academic success. Students with high self – esteem tend to be confident, willing and resilient even when facing academic challenges. The study aimed to assess the self-esteem of high school students in Imphal East district, Manipur. With regards to various socio demographics variables. The study focuses only on students enrolled in class ix and x in the academic session 2025. A total sample of 184 students was drawn using simple random sampling. The sample consisted of 144 female students and 40 male students, representing a diverse mix of learners from different social categories and school environments. Descriptive research method was employed in the study; researchers employed a self-constructed sociodemographic scale to collect the necessary background information. The examination result of the past annual examination was used as the indicator of academic achievement. The Rosenberg Self‑Esteem Scale (RSES, 1965) was employed, the reliability coefficient obtained through Cronbach’s alpha (α = .698). Statistical techniques including descriptive statistics, inferential statistics and Pearson’s correlation coefficient were employed for data analysis. General objective of the study was to find the level of self-esteem. Specific objectives were to compare the self-esteem with regards to male and female, school difference, student status (non-orphan and orphan), school management, present place of residence (home, rented home, hostel and orphanage), academic achievement variation and the relationship between self-esteem and academic achievement. The study found that most students possessed a high sense of self-worth, majority of students fall within the second division category. Their academic performance indicates that there was neither extreme underachievement nor exceptionally high, Pearson’s correlation analysis revealed a very weak negative relationship (r = −0.073). This indicates that higher self-esteem not necessarily led to better academic achievement. Gender-wise comparisons further revealed that there was no statistically significant difference in self-esteem, residential settings, management of schools and academic achievement. Similarly, orphan and non-orphan shows similar levels of self – esteem.